IMPLEMENTASI KEBIJAKAN PELAYANAN PERIZINAN USAHA PERDAGANGAN PADA BADAN PELAYANAN PERIZINAN TERPADU DAN PENANAMAN MODAL DAERAH KOTA BITUNG - PAPULING, DON RAY; MANDEY, JANTJE; POMBENGI, JERICHO (Sam Ratulangi University, 2014)
Abstract : Service public by public bureaucracy represent one the materialization of stateaparatus function as serving society beside as serving state. Service public by meantpublic bureaucracy is secure and prosperous of society (citizen). Therefore, government,specially bureaucracy service of public, owning authority to publish various permit type,shall develop;build mechanism and system service of trustworthy permit so that conductactivity service of permit swiftly is, timely, cheap, transparent and akuntabel. To racegrowth of economics in Town of Bitung, hence government of Town conductbureaucracy reform, specially area service of permit and cultivation of capital as policyinstrument to create climate of effort which kondusif. Pursuant to problems above,writer interest to do research by lifting title : Implementation Policy Service Of Permit isEffort Commerce At Corporation Inwrought Permit And Investation Of Capital AreaTown of Bitung.Keyword : Implementation, Policy Service, Public Services.